Caracterização de formas topográficas em fundos de vale no Planalto de Cascavel, Região Oeste do Estado do Paraná - Ewald, Karl Heins (2013)
Rivers are important agents working in the sculpturing of relief, through its high transport capacity of sediments originary from slopes and marginal erosion. The modeling occurs through the processes of erosion and deposition of sediments, which depend on variables such as lithological composition, slope, and flooding. The processes that originate topographic forms are widely described in the literature of alluvial-bed rivers, however little is known about the occurrence of these forms in mixed bed channels (alluvial-rock) and bedrock channel. In this context, this research aims to describe the topographic forms of the valleys on the Cascavel Plateau. The method for the recognition of these forms is the topographic mapping of cross sections in different parts of the channel located at the top, middle and lower course. The mapping is performed with a set level and optical sights. Were mapped four fluvial channels, two channels in areas with altimetric elevations below 400 meters, and two other channels with elevations above 700 meters. The channels have floodplains with varying lengths. Topographic forms were found as dikes, point bars, flood inundation basins, pools and riffles. The data collected show strong channel incision in the sections corresponding to the upper parts of the channels, and that in the course stretches of low flood plains are well developed. Channel meandering is a characteristic feature of the Cascavel Plateau. The formation of point bars is directly associated with the channel marginal erosion, whereas the dikes are the result of sediment settling. The pool-riffle sequences occur by the reduction of the flow velocity in some places, and, in others, by the presence of woody debris. In some parts of the river where are rock outcrop was observed the formation of pot-holes